Peran Budaya Sekolah Terhadap Masyarakat - Toto Widiarto; Dwi Narsih (Peneliti.net, 2019)
A positive school culture will encourage all school members to work together based on mutual trust, invite the participation of all citizens, encourage the emergence of new ideas, and provide opportunities for the implementation of reforms in schools which all lead to achieving the best results. A good school culture can foster a climate that encourages all school people to learn, which is learning how to learn and study together. A climate will grow that learning is fun and is a necessity, not a compulsion anymore. Learning that arises from self-encouragement, intrinsic motivation, not because of external pressure in all its forms. There will be a growing enthusiasm among school people to always learn about something that has good values. A good school culture can improve school performance, both principals, teachers, students, employees and other school users. This situation will be realized when the cultural qualifications are healthy, solid, strong, positive and professional. Thus an atmosphere of family, collaboration, learning resilience, enthusiasm continues to advance, the drive to work hard and teaching and learning can be created. A good school culture will effectively produce the best performance for each individual, work group / unit and school as an institution, and a synergistic relationship between the three levels. School culture is expected to improve school quality, school performance, and quality of life that are expected to have the characteristics of being healthy, dynamic or active, positive or professional. A healthy school culture provides opportunities for schools and school members to function optimally, work efficiently, energetically, full of vitality, have high enthusiasm, and will be able to continue to develop. Therefore, the culture of this school needs to be developed.